MODEL GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) DALAM PEMBELAJARAN FISIKA PADA POKOK BAHASAN USAHA DAN ENERGI DI SMA - Prety Engestiana; Indrawati Indrawati; Sutarto Sutarto (JURNAL PEMBELAJARAN FISIKA, 2017)
This research focused on the implementation of GI-GI model in learning of physics on the subject of work and energy. The aim of this research are: to study the influence of the model to students’ physics achievement, to describe students’ physics learning activities and students’ retention. A kind of this research is experiment by post test only control group design. The population of this research is students of class XI IPA in SMAN 1 Pakusari and the sample is two classes, XI IPA 4 as an experiment group and XI IPA 5 as a control group. Data collection techniques are documentation, observation, interview and test. Data analysis tecniques to study the influence of the model to students’ physics achievement is independent sample t-test on SPSS 22, to describe students’ physics learning activities and students’ retention use descriptive analysis with percentage. Findings of research are: (1) students’ physics learning activities during the model is 87,9% in very active criteria. (2) students’ physics achievement after using the model showed sig.value (2-tailed) is 0,02 or < 0,05 and it shows that there is a significance difference of student’s physics achievement between the experimental group and control group. (3) Students’ retention after using the model is 109,5% in high category. The research can be concluded that: GI-GI model has a significance influential to the students physics achievement on the subject of work and energy, students’ physics activities included in very active criteria and students’ retention included in high category.